(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Water is scarce in many sections of the nation outside of the monsoon season because of thesignificant concentration of rainfall during those months. Since agriculture in India is so dependent onmonsoon rains, any change in the amount of rain that falls during the season may have far-reachingsocial and economic consequences. The Indian state of Maharashtra includes the Ahmednagar District,which includes the Ahmednagar Tahsil. All of the precipitation information used in this study comesfrom the Ahmednagar district’s statistics department website (MK). There are fourteen tahsil in theAhmednagar District for Shrirampur, Parner, Shrigonda, Karjat, Jamkhed, and Nagar tahsil ofAhmednagar District exhibit declining tendencies (Negative), whereas Akole, Sangamner, Kopergaon,Rahuri, Newasa, Rahata, Shevgaon, and Pathardi tahsil show rising tendencies.